Quality Of Physical Condition Of Youth Pencak Silat Athletes Reviewed From Speed, Power, and Strength - Haris Nugroho; Satria Yudi Gontara; Prayogi Dwina Angga; Gatot Jariono; Inosen Lingsir Maghribi (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
The purpose of this study was to analyze the physical quality of youth pencak silat athletes in terms of speed, power and strength. The sample of this study was athletes Pencak silat category of young male and female numbered 40 people consisting of 20 male and 20 female. Sampling techniques use purposive samples because it considers the characteristics of age and gender. The quasi-experimental method with the quantitative approach used in this research, The constellation of this research is pretest-posttest one group design. Data analysis techniques use descriptive statistics and inferential statistics. Descriptive analysis aims to describe the characteristics of this research while inferential analysis using paired one sample test at a significant level ?= 0.05, overall data analysis used is SPSS program version 20.0. The results of this study showed that the quality of physical condition of athletes in the youth competition category is reviewed from speed, power, and strength in the good category. However, in this study, the need to further identify anthropometrics, and psychology athletes to determine the achievements of adolescent martial arts match categories according to gender characteristics.